TEMPAT RETRET KOTA - Vincent Tan; Alvin Hadiwono (Jurusan Arsitektur dan Perencanaan, 2019)
This world has created major changes, this is considered as the impact of the current globalization that cannot be stopped anymore. This stream of globalization has caused stress for the millennial generation. Millennials are those that are affected by this current, the largest - with their birth in 1981-2000. They are also people of productive age. Research from the Mental Health Foundation (MHF, 2018) found millennials were more stressed than other older age groups such as generation X. This attracted attention to mental and physical health, especially spiritual issues to overcome this. The purpose of this project is to introduce a new type of place of spirituality in the millennial generation, to open new understandings and thoughts about spirituality in architecture, to produce architectural works that support new changes in the millennial generation, and to increase awareness in the millennial pre-post architectural direction future spirituality. Theoretical study that underlies this design project is taken from Suzan Caroll's book entitled Seven Steps to Soul and the method used is Thematic Narrative Architecture. Thematic Approach Narrative Architecture is a design approach by telling a process that considers the application of themes as elements in a building. This approach is supported by other sub-methods, namely Spatial Gestalts, Experiential Archetypes and Reference. This design project brings users into a spiritual experience that aims to become a place of self-release for all people, especially millennials. Abstrak Dunia ini telah menciptakan perubahan besar, hal ini dianggap sebagai dampak dari arus globalisasi yang sudah tidak dapat dibendung lagi. Arus globalisasi ini mengakibatkan stress bagi generasi milennial. Milennial adalah mereka yang terkena dampak arus ini terbesar -dengan kelahirannya pada tahun 1981-2000. Mereka juga adalah orang-orang dengan usia produktif. Penelitian dari Mental Health Foundation (MHF, 2018) menemukan generasi milenial lebih stres dibandingkan kelompok usia lain yang lebih tua seperti generasi X. Hal ini menarik perhatian akan hal kesehatan mental serta fisik khususnya spiritual untuk menanggulangi ini. Adapun tujuan dari proyek ini yaitu mengenalkan tipe baru tempat spiritualitas pada jaman generasi milennial, membuka pengertian dan pemikiran baru tentang spiritualitas dalam arsitektur, menghasilkan karya arsitektur yang mendukung perubahan baru pada jaman generasi milennial, dan meningkatkan awareness pada generasi sebelum-sesudah millennial akan arahan arsitektur spiritualitas kedepan. Kajian Teori yang mendasari proyek desain ini diambil dari buku Suzan Caroll yang berjudul Seven Steps to Soul dan metode yang digunakan adalah Thematic Narrative Architecture.Pendekatan Thematic Narrative Architecture adalah pendekatan desain dengan menceritakan sebuah proses yang memperhatikan penerapan tema sebagai unsur-unsur pada bangunan. Pendekatan ini didukung oleh sub-metode lainnya yaitu Spatial Gestalts, Experiential Archetypes dan Reference. Proyek rancangan ini membawa pengguna kedalam sebuah pengalaman spiritual yang bertujuan untuk menjadi tempat pelepasan diri bagi semua orang khususnya millennial.